Efektivitas Perangkat Pembelajaran Berbasis Literasi Sains Untuk Meningkatkan Literasi Sains Siswa SMP - Muhammad Novaldy Nur Dwinanda Wahab; Wasis; Yuliani (Jurnal Penelitian Pendidikan IPA, 2024)
The researcher's goal in this study is to investigate the efficiency of the scientific literacy-based learning device model learning cycle 7E in improving student scientific literacy skills. This research used Research and development, with one group pretest-posttest design and two replications. The research sample was VII-grade junior high school students. To gather data about students’ scientific literacy, the researcher used a scientific literacy-based test. The data on students' scientific literacy will be evaluated to determine their level and skills before and after treatment with the development product. Based on research analysis and findings after using a scientific literacy-based learning device, the students’ scientific literacy increased. It can be seen from the n-gain value average obtained in junior high school 2, which has a value of 0.72 and is categorized as high. Meanwhile, the trial class of junior high school 2, was also categorized as high, with a value of 0.71. The results of a statistical test using two independent t-tests showed no significant difference between the n-gain values of the two trial classes. Based on these findings, it can be stated that the scientific literacy-based learning device model learning cycle 7E, helps increase students' scientific literacy.